Replication Stress Impairs Chromosome Segregation and Preimplantation Development in Human Embryos. Issue 11 (November 2022) - Palmerola, Katherine L.; Amrane, Selma; De Los Angeles, Alejandro; Xu, Shuangyi; Wang, Ning; de Pinho, Joao; Zuccaro, Michael V.; Taglialatela, Angelo; Massey, Dashiell J.; Turocy, Jenna; Robles, Alex; Subbiah, Anisa; et al.
Abstract : (Abstracted from Cell 2022;185:2988.e20–3007.e20) Spontaneous DNA damage, such as double-strand breaks (DSBs), affects cell-cycle progression and contributes to embryo attrition. There is a strong correlation among mitotic cell-cycle progression, ploidy, the quality of the blastocyst formed, and successful implantation from in vitro fertilization.